2020
DOI: 10.1017/s1463423620000250
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol on Enhanced Primary Healthcare (EnPHC) interventions: a quasi-experimental controlled study on diabetes and hypertension management in primary healthcare clinics

Abstract: Aim: This paper describes the study protocol, which aims to evaluate the effectiveness of a multifaceted intervention package called ‘Enhanced Primary Healthcare’ (EnPHC) on the process of care and intermediate clinical outcomes among patients with Type 2 diabetes mellitus (T2DM) and hypertension. Other outcome measures include patients’ experience and healthcare providers’ job satisfaction. Background: In 2014, almost two-thirds of Malaysia’s adult population aged 18 years or older had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The clinics were selected by the study team based on their setup and size that reflects care services provided across public health clinics, along with budget and capacity to implement the EnPHC package. Details about the EnPHC project have been described and published elsewhere ( Sivasampu et al, 2020 ). In summary, patients aged 30 years and older with a recorded diagnosis of T2DM or hypertension were sampled from the participating clinics.…”
Section: Methodsmentioning
confidence: 99%
“…The clinics were selected by the study team based on their setup and size that reflects care services provided across public health clinics, along with budget and capacity to implement the EnPHC package. Details about the EnPHC project have been described and published elsewhere ( Sivasampu et al, 2020 ). In summary, patients aged 30 years and older with a recorded diagnosis of T2DM or hypertension were sampled from the participating clinics.…”
Section: Methodsmentioning
confidence: 99%
“…The extracted data included demographics (age, gender, ethnicity), risk factors (comorbidities, duration of disease), and laboratory investigation (HbA1c). 13…”
Section: Methodsmentioning
confidence: 99%
“…The extracted data included demographics (age, gender, ethnicity), risk factors (comorbidities, duration of disease), and laboratory investigation (HbA1c). 13 2. Medication data were obtained from the Pharmacy Information System (PhIS), an electronic medication management system implemented in the public primary care clinics.…”
Section: Study Design and Data Sourcementioning
confidence: 99%
“…The EnPHC interventions implemented in the 20 intervention clinics beginning in July 2017 encompassed: i) an Integrated Care Pathway (ICP); ii) a patient visit checklist; iii) Integrated Specialized Services (ISS) by allied health professionals; iv) NCD screening and cardiovascular risk strati cation; v) an NCD care form; vi) the Family Health Teams (FHT) concept; vii) involvment of a care coordinator; viii) pharmacist-led Cardiovascular Care Bundle Medication Therapy Adherence Clinic (CCBMTAC); ix) clinical and prescribing audits; and x) structured communication across primary and secondary care levels with a fast track referral system. Further details on the study design and EnPHC interventions have been described elsewhere [8].…”
Section: Enphc Interventionsmentioning
confidence: 99%
“…Increasing engagement at all levels of the cascade may allow early detection and minimise morbidity and mortality from diabetes. A previous cascade of care analysis revealed that as many as 50% of individuals with type 2 diabetes in Malaysia were undiagnosed and even after receiving a diagnosis, only 22% had good glycemic control [8].…”
Section: Introductionmentioning
confidence: 99%